Electrical‐Triggered Multicolor Reversible Color‐Changing Ag Nanoparticles/Reduced Graphene Oxide/Polyurethane Conductive Fibers. Issue 1 (3rd October 2022) - Zhang, Ningyi; Cheng, Haonan; Han, Weiyi; Ge, Fangqing; Yin, Yunjie; Wang, Chaoxia
Abstract: Smart color‐changing fibers attract much attention owing to their importance as a component of flexible electronics. A facile and scalable method of multicolor reversible electro–thermochromic Ag nanoparticles/reduced graphene oxide/polyurethane conductive fiber (ETC AgNPs/rGO/PU conductive fiber) is fabricated, which contains the polyurethane (PU) as the inner layer, reduced graphene oxide (rGO) with Ag nanoparticles (AgNPs) as the conductive layer, and thermochromic paste as the outermost layer. It possesses excellent electrothermal and color‐changing properties and rapidly generates Joule heat at 0.5 V, which makes the fiber surface temperature reach 39.81 °C rapidly. The color switching rate is fast and changes from green to yellow within 2 s. During the process of 250 times on/off voltage, ETC AgNPs/rGO/PU conductive fibers still maintain excellent electrical and thermal properties and color change stability; even in the washing, strong acid, and strong alkali environment, they still have excellent durability. This human subjective adjustable electrical–thermal–color multi‐level induced modulation makes it possible to be applied to smart wearable fields such as visual camouflage, personal thermal management, and active information transfer. Abstract : This paper reports a facile and scalable method for multicolor reversible electro–thermochromic AgNPs/rGO/PU conductive fibers. The internal reduced graphene oxide and Ag nanoparticles are used as the conductive layer to provide an electric heat source for the external thermochromic layer to achieve the effect of electrothermal color‐changing. It maintains excellent electro–thermochromic properties and color‐changing stability.